A PHILOSOPHICAL STUDY OF SRIRAMCHARITMANAS VIA KIERKEGAARD’S EXISTENTIALISM - Pravara Sonawane (International Journal of Social Studies, 2025)
Philosophy, as B. Charles Henry articulates, serves as a bridge between historical foundations, contextual relevance, and contemporary reality, offering profound insights into human expectations and outcomes. It shapes moral judgment, rational discourse, and the pursuit of knowledge in meaningful ways (Henry, p. 593). This research paper applies this philosophical perspective to Tulsidas’s Sri Ramcharitmanas, analyzing its continued relevance in the modern world. The text, deeply rooted in the Bhakti tradition, offers insights into human perseverance, faith, and the struggle between spiritual surrender and existential challenges. A central theme explored in this paper is the human tendency to experience fatigue, despair, and the possibility of giving up, particularly in the face of adversity. This theme is examined through the lens of Bhakti (devotional surrender) and the existential philosophy of Søren Kierkegaard. By employing Kierkegaard’s theory of subjectivity, this study investigates how the dilemmas presented in Sri Ramcharitmanas mirror modern existential concerns—such as the search for meaning, personal responsibility, and the balance between faith and free will.Moreover, the paper delves into the duality of the doha (couplets) in Sri Ramcharitmanas and their philosophical implications in today’s world. The juxtaposition of devotion (bhakti) and personal struggle within these verses resonates with contemporary existential thought. To further substantiate these ideas, the research incorporates Indian philosophical aesthetics, exploring how Tulsidas employs poetic and narrative techniques to convey deeper truths about human existence. Through this interdisciplinary approach, the paper highlights how Sri Ramcharitmanas is not just a religious scripture but also a profound philosophical text that continues to offer guidance on existential and spiritual dilemmas in the modern era.